β-Tubulin Isotype, TUBB4B, Regulates The Maintenance of Cancer Stem Cells - Dharmapal, Dhrishya; Jyothy, Athira; Mohan, Amrutha; Balagopal, P. G.; George, Nebu Abraham; Sebastian, Paul; Maliekal, Tessy Thomas; Sengupta, Suparna (Frontiers in Oncology, 2021)
Recent advancements in cancer research have shown that cancer stem cell (CSC) niche is a crucial factor modulating tumor progression and treatment outcomes. It sustains CSCs by orchestrated regulation of several cytokines, growth factors, and signaling pathways. Although the features defining adult stem cell niches are well-explored, the CSC niche is poorly characterized. Since membrane trafficking proteins have been shown to be essential for the localization of critical proteins supporting CSCs, we investigated the role of TUBB4B, a probable membrane trafficking protein that was found to be overexpressed in the membranes of stem cell enriched cultures, in sustaining CSCs in oral cancer. Here, we show that the knockdown of TUBB4B downregulates the expression of pluripotency markers, depletes ALDH1A1+ population, decreases in vitro sphere formation, and diminishes the tumor initiation potential in vivo. As TUBB4B is not known to have any role in transcriptional regulation nor cell signaling, we suspected that its membrane trafficking function plays a role in constituting a CSC niche. The pattern of its expression in tissue sections, forming a gradient in and around the CSCs, reinforced the notion. Later, we explored its possible cooperation with a signaling protein, Ephrin-B1, the abrogation of which reduces the self-renewal of oral cancer stem cells. Expression and survival analyses based on the TCGA dataset of head and neck squamous cell carcinoma (HNSCC) samples indicated that the functional cooperation of TUBB4 and EFNB1 results in a poor prognosis. We also show that TUBB4B and Ephrin-B1 cohabit in the CSC niche. Moreover, depletion of TUBB4B downregulates the membrane expression of Ephrin-B1 and reduces the CSC population. Our results imply that the dynamics of TUBB4B is decisive for the surface localization of proteins, like Ephrin-B1, that sustain CSCs by their concerted signaling.